2018
DOI: 10.1002/clc.23074
|View full text |Cite
|
Sign up to set email alerts
|

Switching from ticagrelor to clopidogrel in patients with ST‐segment elevation myocardial infarction undergoing successful percutaneous coronary intervention in real‐world China: Occurrences, reasons, and long‐term clinical outcomes

Abstract: Switching from ticagrelor to clopidogrel is very common in patients with STEMI in China. De-escalation might be safe but associated with high risk of ischemic events as compared to ticagrelor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…After exclusion of 874 studies by title and/or abstract, 36 articles were reviewed in full‐text. Finally, 14 studies 8,14‐26 that met all criteria were included in our meta‐analysis (Figure 1), with 46 983 participants. The duration of follow‐up was 11.1 ± 2.9 months, ranging from 6 to 15 months.…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of 874 studies by title and/or abstract, 36 articles were reviewed in full‐text. Finally, 14 studies 8,14‐26 that met all criteria were included in our meta‐analysis (Figure 1), with 46 983 participants. The duration of follow‐up was 11.1 ± 2.9 months, ranging from 6 to 15 months.…”
Section: Resultsmentioning
confidence: 99%
“…It may be considered an effective and practical strategy to reduce ischemic and bleeding events in elderly patients [37]. This recommendation is supported by several studies where ticagrelor was switched to clopidogrel in ACS patients undergoing PCI [38][39][40]. Still, the effectiveness and safety of this switching require more studies to determine the appropriate time for switching.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 3 ] De-escalation (change from ticagrelor or prasugrel to clopidogrel) may be required due to major bleeding, ambiguity surrounding dose requirements for elderly patients/patients with low body weight using prasugrel, or cost. [ 51 53 ]…”
Section: Switching Antiplatelet Therapymentioning
confidence: 99%
“…[ 54 ] However, observational data from Asian patients have suggested that de-escalating DAPT in the absence of platelet-function-testing-guided clopidogrel dosing may increase the risk of ischaemic events without reducing bleeding risk. [ 38 , 51 , 53 , 55 ]…”
Section: Switching Antiplatelet Therapymentioning
confidence: 99%